2014
DOI: 10.1002/smll.201401770
|View full text |Cite
|
Sign up to set email alerts
|

A Full Compositional Range for a (Ga1-xZnx)(N1-xOx) Nanostructure: High Efficiency for Overall Water Splitting and Optical Properties

Abstract: Bulk (Ga1-x Zn x )(N1-x O x ) as a photocatalyst has received increasing attention as a potential solution for the energy shortage challenge; however, its catalytic performance is highly limited by its bulk form. To improve the photochemical potential, the nanoscale form of this multiple-metal oxynitrides is desirable. In this work, a new type of (Ga1-x Zn x )(N1-x O x ) nanostructure is obtained. Its composition can tuned to the full range (0.18 < x < 0.95). The (Ga1-x Zn x )(N1-x O x ) nanostructure exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
6
68
0
Order By: Relevance
“…They found that the Fe dopants were inclined to be located at the interstitial site when the ZrO 2 was in a cubic phase. 21,22 The preparation detail information could be seen in the experimental information. 19 Furthermore, due to the high sintering temperature, the dopants always precipitated from the ZrO 2 structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the Fe dopants were inclined to be located at the interstitial site when the ZrO 2 was in a cubic phase. 21,22 The preparation detail information could be seen in the experimental information. 19 Furthermore, due to the high sintering temperature, the dopants always precipitated from the ZrO 2 structure.…”
Section: Resultsmentioning
confidence: 99%
“…As well known, the nanomaterials have small size and high surface energy which can always reduce the reaction temperature signicantly. 20,21,23 First, the hollow sphere morphology had a high specic surface area, which meant that more areas could be illuminated. Our strategy for synthesizing Fe doped ZrO 2 nanostructures was based on the calculation results above and our previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Briey, carbon spheres were rst synthesized using the method reported by Li et al 22 Then zinc nitrate hexahydrate (Zn(NO 3 ) 2 $6(H 2 O), 99% purity, 10 mmol) and iron(III) nitrate nonahydrate (Fe(NO 3 ) 3 $9H 2 O, 99% purity, 1 mmol) were dissolved in 200 mL of DMF (N,N-dimethylformamide, 99.8% purity). [19][20][21] Briey, carbon spheres were rst synthesized using the method reported by Li et al 22 Then zinc nitrate hexahydrate (Zn(NO 3 ) 2 $6(H 2 O), 99% purity, 10 mmol) and iron(III) nitrate nonahydrate (Fe(NO 3 ) 3 $9H 2 O, 99% purity, 1 mmol) were dissolved in 200 mL of DMF (N,N-dimethylformamide, 99.8% purity).…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
“…Such large bowings have been observed in other material system such as (ZnO) 1-x (GaN) x and (ZnO) 1-x (AlN) x . [24][25][26][27] Additionally, for N-alloyed Ga 2 O 3 , the effects of phase transition may need to be considered. The introduction of N into Ga 2 O 3 will lift up the valence band.…”
mentioning
confidence: 99%